2020
DOI: 10.1016/j.scitotenv.2020.139040
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of apparent temperature on daily emergency visits for mental and behavioral disorders in Beijing, China: A time-series study

Abstract: Background The relationship between temperature and mental disorders is still unclear. This study aims to assess the short-term effect of apparent temperature (AT) on daily emergency visits of mental and behavioral disorders (MDs) in Beijing, China. Methods Daily counts of emergency visits related to MDs in Beijing from 2016 to 2018 were obtained. A quasi-Poisson generalized additive model combined with a distributed lag non-linear model (DLNM) was applied to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…These results are obtained by using AT instead of the individual parameters WS, T, HP, and WP to better summarize the results. Furthermore, AT has been proven to characterize the physiological experience better than just the temperature or the other parameters alone [Niu et al ( 27 )]. In our case, SR, AT, and PM 2.5 are very closely related to the HLSA and male subjects while LLSA and females are correlated to NO 2 concentration and precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are obtained by using AT instead of the individual parameters WS, T, HP, and WP to better summarize the results. Furthermore, AT has been proven to characterize the physiological experience better than just the temperature or the other parameters alone [Niu et al ( 27 )]. In our case, SR, AT, and PM 2.5 are very closely related to the HLSA and male subjects while LLSA and females are correlated to NO 2 concentration and precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, other environmental variables such as increased ambient temperature or air pollution could be implicated in this complex phenomenon. A potential role of ambient or apparent temperature on suicidal behaviors has been studied with controversial results (15,16,(23)(24)(25)(26)(27)(28). Several data, however, showed that a 26.6-60% of variation in suicidal behaviors could be explained by temperature fluctuations (29-31) but not with sunlight exposure, especially in completed suicide (16).…”
Section: Introductionmentioning
confidence: 99%
“…The AT was calculated by daily mean temperature, relative humidity, and barometric pressure using the following equations ( 18 , 22 , 23 ):…”
Section: Methodsmentioning
confidence: 99%
“…According to the above meteorological data, which include ambient temperature, wind velocity and relative humidity, AT was calculated. The specific formulas used are as follows [18,19]: where T a represents the ambient mean temperature (°C); ɑ is vapour pressure (hPa), calculated using equation (2); WV is wind velocity (m s −1 ), and RH is relative humidity (%).…”
Section: Calculation Of Atmentioning
confidence: 99%